Aicardi–Goutières syndrome: a model disease for systemic autoimmunity. (3rd December 2013) - Lee-Kirsch, M A; Wolf, C; Günther, C
Summary: Systemic autoimmunity is a complex disease process that results from a loss of immunological tolerance characterized by the inability of the immune system to discriminate self from non-self. In patients with the prototypic autoimmune disease systemic lupus erythematosus (SLE), formation of autoantibodies targeting ubiquitous nuclear antigens and subsequent deposition of immune complexes in the vascular bed induces inflammatory tissue injury that can affect virtually any organ system. Given the extraordinary genetic and phenotypic heterogeneity of SLE, one approach to the genetic dissection of complex SLE is to study monogenic diseases, for which a single gene defect is responsible. Considerable success has been achieved from the analysis of the rare monogenic disorder Aicardi–Goutières syndrome (AGS), an inflammatory encephalopathy that clinically resembles in-utero -acquired viral infection and that also shares features with SLE. Progress in understanding the cellular and molecular functions of the AGS causing genes has revealed novel pathways of the metabolism of intracellular nucleic acids, the major targets of the autoimmune attack in patients with SLE. Induction of autoimmunity initiated by immune recognition of endogenous nucleic acids originating from processes such as DNA replication/repair or endogenous retro-elements represents novel paradigms of SLE pathogenesis. These findings illustrate how investigating rare monogenic diseases can also fuel discoveries that advance our understanding of complex disease. This will not only aid the development of improved tools for SLE diagnosis and disease classification, but also the development of novel targeted therapeutic approaches.